Transforming online classroom management to enhance elementary students’ learning motivation - Riadi, Fadhilah Salsabila; Sukmalia, Maulida; Zainab, Meisya Siti; Prihantini, Prihantini (Jurnal Pembangunan Pendidikan: Fondasi dan Aplikasi, 2024)
Implementing online learning requires adaptation and habituation, which presents various obstacles for teachers and students. These obstacles can reduce students’ learning motivation. Therefore, an effective learning strategy is needed to increase primary school students’ learning motivation. This research examines the reorientation and revitalization of classroom management in online learning to increase primary school students’ learning motivation. The qualitative research method uses literature study techniques from various relevant sources. The results show that effective classroom management can increase students’ motivation in online learning. This includes applying the principles of classroom management, organizing the classroom environment, creating a positive atmosphere, applying clear rules, and good communication between teachers and students, with the teacher acting as a facilitator. Good classroom management can increase students’ learning motivation and make learning more purposeful. In addition, parents’ contribution in guiding and accompanying students during online learning from home is also important to achieve optimal results. This research contributes to the understanding of the importance of classroom management in online learning to increase students’ learning motivation. In addition, this research provides practical guidance for teachers and parents, equipping them with the necessary tools and strategies to create an effective and supportive learning environment during the online learning period. The results of this study are expected to serve as a reference for future educational policies and learning practices, helping to create superior and globally competitive human resources in accordance with the objectives of various human resource improvement workshops that have been implemented.